Jawabanmu

2014-03-01T12:27:32+07:00
Pertama kerjakan dulu (g-¹ • f-¹) (x) jadikan (g•f)-¹ (x) jadi  kerjaka dulu komposisisnya baru di invers.
 (g(f(x))) 
(g(x+5) = x+2/2x+3
           = (x+5)+2/2(x+5)+3
           = x+7/2x+13
nah baru deh di invers (x+7/2x+13) jadinya :
-13x+7/2x-1 

cmiiw :)
2014-03-01T13:32:42+07:00
F(x) = x + 5
f^-1(x) = x + 5
y = x + 5
y-5=x
f^-1=x-5

g(x)=x+2/2x+3
y=x+2/2x+3
2xy+3y=x+2
2xy-x=2-3y
x(2y-1)=2-3y
x=2-3y/2y-1
g^-1(x)=2-3x/2x-1

jadi (g^-1 . f^-1)(x)
2-3(x-5)/2(x-5)-1 = 2-3x+15/2x-10-1 = 2-3x +15 / 2x-11